Cover Image. (20th January 2022) - Lento, Jennifer; Culp, Joseph M.; Levenstein, Brianna; Aroviita, Jukka; Baturina, Maria A.; Bogan, Daniel; Brittain, John E.; Chin, Krista; Christoffersen, Kirsten S.; Docherty, Catherine; Friberg, Nikolai; Ingimarsson, Finnur; et al.
Abstract : The cover image is based on the Original Article Temperature and spatial connectivity drive patterns in freshwater macroinvertebrate diversity across the Arctic, by Jennifer Lento et al . https://doi.org/10.1111/fwb.13805 .